Double Layer Collimator for BNCT Neutron Source Based on 30 MeV Cyclotron - Bilalodin Bilalodin; Kusminarto Kusminarto; Arief Hermanto; Yohannes Sardjono; Sunardi Sunardi (Indonesian Journal of Physics and Nuclear Applications, 2017)
A research of design of double layer collimator using 9Be(p,n) neutron source has been conducted. The research objective is to design a double layer collimator to obtain neutron sources that are compliant with the IAEA standards. The approach to the design of double layer collimator used the MCNPX code. From the research, it was found that the optimum dimensions of a beryllium target are 0.01 mm in length and 9.5 cm in radius. Collimator consists of a D2O and Al moderator, Pb and Ni as a reflector, and Cd and Fe as a thermal and fast neutron filter. The gamma filter used Bi and Pb. The quality neutron beams emitted from the double layer collimator is specified by five parameters: epithermal neutron flux 1 ×109 n/cm2s; fast neutron dose per epithermal neutron flux 5 ×1013 Gy cm2s; gamma dose per epithermal neutron flux 1×1013 Gy cm2s; ratio of the thermal neutron flux of epithermal neutron flux 0; and the ratio of epithermal neutron current to total epithermal neutron 0.54.